2011
DOI: 10.1016/j.schres.2011.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of self-reported medical problems in patients with alcohol dependence and co-occurring schizophrenia or schizoaffective disorder

Abstract: Background Schizophrenia and alcohol dependence (AD) are both major risk factors for a variety of medical problems, yet little is known about the medical status of patients in whom both conditions coexist. Objective To assess accuracy of self-reported medical problems and to compare the accuracy reports in patients with schizophrenia or schizoaffective disorder and co-occurring AD compared to patients with AD only and to controls. Our hypothesis was that medical problems are under-reported in patients with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…In the National Treatment Improvement Evaluation Study (NTIES; Meszaros et al, 2011), substantial reductions in use of both crack and cocaine powder were found following treatment, with roughly a 50% reduction in the number of participants reporting drug use through either route (without differences between them) during the 12-months before and after treatment (Richard W. Foltin, Fischman, & Levin, 1995). Data from the National Treatment Outcome Research Study (NTORS; Gunter, Philibert, & Hollenbeck, 2009) indicated significant increases in cocaine abstinence rates at 1-year following treatment for both crack and powder cocaine users in residential treatment, but abstinence rates at the 4-5 year follow-up time point were maintained for cocaine powder users only, whereas crack users abstinence rates returned to the rates at intake (Stein, 1999).…”
mentioning
confidence: 99%
“…In the National Treatment Improvement Evaluation Study (NTIES; Meszaros et al, 2011), substantial reductions in use of both crack and cocaine powder were found following treatment, with roughly a 50% reduction in the number of participants reporting drug use through either route (without differences between them) during the 12-months before and after treatment (Richard W. Foltin, Fischman, & Levin, 1995). Data from the National Treatment Outcome Research Study (NTORS; Gunter, Philibert, & Hollenbeck, 2009) indicated significant increases in cocaine abstinence rates at 1-year following treatment for both crack and powder cocaine users in residential treatment, but abstinence rates at the 4-5 year follow-up time point were maintained for cocaine powder users only, whereas crack users abstinence rates returned to the rates at intake (Stein, 1999).…”
mentioning
confidence: 99%
“…Among older patients with schizophrenia, diabetes is highly prevalent (about 25% of patients), especially among women ( Annamalai et al, 2017 ; Huo et al, 2021 ), with a 2 to 5-fold increased risk than in the general population ( Annamalai et al, 2017 ; Mamakou et al, 2018 ). Similarly, these patients are at higher risk for hypertension ( Meszaros et al, 2011 ; Mamakou et al, 2018 ), obesity ( Allison et al, 2009 ; Annamalai et al, 2017 ), and dyslipidemia ( Mamakou et al, 2018 ). The higher risk of schizophrenia patients for these comorbidities can be explained by the physiopathology of the disease itself and the utilization of psychotropic medications ( Mitchell et al, 2013 ; Abosi et al, 2018 ; Mamakou et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Employment status is a predictor of violent behaviour among persons with schizophrenia, as evidenced by its inclusion as a factor in clinical tools used to predict violence in this patient population (Meszaros et al, 2011). One investigation found that persons with a serious mental illness including schizophrenia are at increased risk of exhibiting violent behaviour if they have experienced some type of financial crisis (Elbogen, Dennis, & Johnson, 2016).…”
Section: Employmentmentioning
confidence: 99%